2016
DOI: 10.2196/jmir.5498
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Internet Use and Ambulatory Care-Seeking Behaviors in Taiwan: A Cross-Sectional Study

Abstract: BackgroundCompared with the traditional ways of gaining health-related information from newspapers, magazines, radio, and television, the Internet is inexpensive, accessible, and conveys diverse opinions. Several studies on how increasing Internet use affected outpatient clinic visits were inconclusive.ObjectiveThe objective of this study was to examine the role of Internet use on ambulatory care-seeking behaviors as indicated by the number of outpatient clinic visits after adjusting for confounding variables.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…Mass media sources could potentially play a role in raising awareness about health care services and in shaping the perceptions of health care and related decision-making [ 30 , 31 ]. Similar findings in previous reports provide strong evidence to support this point.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mass media sources could potentially play a role in raising awareness about health care services and in shaping the perceptions of health care and related decision-making [ 30 , 31 ]. Similar findings in previous reports provide strong evidence to support this point.…”
Section: Discussionmentioning
confidence: 99%
“…In 2008, Lee et al [ 1 ] reported that the increasing use of the Internet was correlated with an increase in outpatient clinic visits after controlling for age and sex in a data analysis. Other authors have also elucidated a significant association between use of health information technology and health services use [ 29 , 31 , 32 ]. First, we recognized that the availability of health information in mass media sources has triggered the health care interest of the general population [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…We also highlighted the possibility that the media literacy of the audience, i.e. patients, family members, and health care workers, might play an important role on medical decision-making, as well as decision-making to initiate, withhold, or withdraw LSTs [ 35 ]. By further stratifying into different sub-populations, we found that the ECMO use was significantly increased following 2006 in both gender groups and in the adult population.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that Internet users utilized more ambulatory care [16], and were more likely to change medical decisions [17]. Furthermore, people who used the Internet were more likely to actively participate in medical decision-making than those who did not use the Internet, and people who searched for online health information were more likely to actively participate in medical decision-making than those who did not use the…”
Section: Social Media and Active Participation In Medical Decision-mamentioning
confidence: 99%
“…Widely available modern information technology has dramatically changed peoples' access to medical information, shifting access from non-interactive and traditional media, such as newspaper, magazine, television, radio and so on, to that of the interactive, web-2.0 internet-based social media such as Facebook, Twitter, WhatsApp, LINE and the like. Studies have overwhelmingly pointed out the association between health information in the media [12][13][14] and the usage of medical treatments and interventions, not only in the intensive and critical care medical encounters [15], but also in those of ambulatory care [16].Given that online health information indeed changes people's medical decision-making [17], incorrect online health information can result in a heavy burden in medical encounters …”
mentioning
confidence: 99%